Global Simulations of the Inner Regions of Protoplanetary Disks with Comprehensive Disk Microphysics - Bai, Xue-Ning (The Astrophysical journal, 2017)
The gas dynamics of weakly ionized protoplanetary disks (PPDs) are largely governed by the coupling between gas and magnetic fields, described by three non-ideal magnetohydrodynamical (MHD) effects (Ohmic, Hall, ambipolar). Previous local simulations incorporating these processes have revealed that the inner regions of PPDs are largely laminar and accompanied by wind-driven accretion. We conduct 2D axisymmetric, fully global MHD simulations of these regions (∼1-20 au), taking into account all non-ideal MHD effects, with tabulated diffusion coefficients and approximate treatment of external ionization and heating. With the net vertical field aligned with disk rotation, the Hall-shear instability strongly amplifies horizontal magnetic field, making the overall dynamics dependent on initial field configuration. Following disk formation, the disk likely relaxes into an inner zone characterized by asymmetric field configuration across the midplane, which smoothly transitions to a more symmetric outer zone. Angular momentum transport is driven by both MHD winds and laminar Maxwell stress, with both accretion and decretion flows present at different heights, and modestly asymmetric winds from the two disk sides. With anti-aligned field polarity, weakly magnetized disks settle into an asymmetric field configuration with supersonic accretion flow concentrated at one side of the disk surface, and highly asymmetric winds between the two disk sides. In all cases, the wind is magneto-thermal in nature, characterized by a mass loss rate exceeding the accretion rate. More strongly magnetized disks give more symmetric field configuration and flow structures. Deeper far-UV penetration leads to stronger and less stable outflows. Implications for observations and planet formation are also discussed.